Assessing Future Flood Hazards for Adaptation Planning in a Northern European Coastal Community - Sorensen, Carlo; Broge, Niels H.; Molgaard, Mads R.; Schow, Charlotte S.; Thomsen, Peter; Vognsen, Karsten; Knudsen, Per (Frontiers in Marine Science, 2016)
From a transdisciplinary approach in the town of Thyboron, Denmark, we investigate couplings between sea state (i.e., mean and extreme) and flooding hazards today and ahead. This includes analyses of change and variability in the groundwater table, precipitation, land motion, geotechnical ground properties, sewerage systems and other infrastructure to outline a more complete platform for the integration of knowledge into climate adaptation schemes at this highly vulnerable coastal location. It involves the engagement of the main stakeholders who, although having different responsibilities, interests, needs of knowledge and data, and different timeframes for investment and planning, must join in a common appraisal of the challenges faced ahead to provide for better adaptation measures. Apart from obvious adverse effects from future storm surge events, knowledge about the coupled effects of the abovementioned parameters needs to be taken into account to reach optimal mitigation and adaptation measures. Through stakeholder interviews it becomes clear that an enhanced focus on transdisciplinary research is a viable way forward to develop such measures: it will bring in more knowledge, a broader scope, and it will provide for more holistic solutions that both serve to protect the town and allow for business development and better municipal planning ahead.